Adherence among parents on under-five childhood immunization schedule: a review - Mohd Zulkefli, Nor Afiah; Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2016)
Background: Adherence on under-five childhood immunization schedule has been an area of study that has seldom been explored. Adherence has been the subject of focus in determine if the results of outbreaks and vaccine preventable disease is related to the adherence of the parents to the vaccine schedule. Materials and Methods: A systematic review of articles on the factors of adherence on under-five childhood immunization schedule was performed using various keywords utilizing multiple databases (Medline, PubMed, Science Direct and CINAHL). Studies conducted between 2000 to present, English language and were either observational or qualitative designs were included. Result: Of 45 articles identified, 13 studies were eligible for inclusion. The studies showed that the majority of factors were divided into modifiable and non-modifiable factors. These factors were then further classified into various groups according to its relevance. The modifiable factors were identified as knowledge, vaccine, awareness and perception towards childhood immunization. Whereas non-modifiable factors were sociodemographic factors of parent and child, logistic factors and administration factors. Conclusion: There were many factors identified significantly to be associated with adherence among parents on under-five childhood immunization schedule.